An Anatomy of Accountability at the WTO. Issue 1 (21st July 2014) - Wolfe, Robert
Abstract Accountability is fundamental to democratic governance and good administration, but its multiple meanings and claimants challenge international organizations. Who is accountable implies who can be accountable, and the matters for which some process exists to hold them accountable through some effect on their behavior. The answers to those questions in the World Trade Organization (WTO) will differ depending on who is asking and on the values to be promoted, from international order, procedural fairness, prosperity and justice to sustainable development. An anatomy of accountability in the WTO finds many possible 'accountability regimes', illuminating the tension between vertical and horizontal accountability (domestic responsiveness and international obligation) and the challenge in choosing among horizontal accountability regimes (promise keeping by members): efforts to satisfy any one accountability claim can make achieving the others more difficult.